Poverty alleviation policies, programs and practices for people with disabilities: A scoping review and recommendations. - Sally Lindsay; Janice Phonepraseuth; Sarah Leo (PLoS ONE)
Background People with disabilities have a higher prevalence of living in poverty compared to people without disabilities, which largely results from the challenges, barriers, inequalities and discrimination they often encounter. However, little is known about relevant policies, practices, and anti-poverty interventions that could facilitate a better quality of life for people with disabilities. Methods A scoping review following the Joanna Briggs Institute methodology was used to explore the existing practices, policies and interventions to address poverty among people with disabilities. The search involved six international databases: Ovid Medline, Healthstar, PsychINFO, Econlit, Scopus and Web of Science where two reviewers screened 4548 studies for inclusion. Results Thirty-seven studies were included in the review, which spanned across 20 countries. Our review noted the following key trends: (1) poverty alleviation policies; (2) programs and practices to address poverty (e.g., benefits, barriers and factors affecting access); and (3) cash transfers, especially their impact and factors affecting transfers. Conclusions The findings of this review underscore the potential value of poverty alleviation strategies and policies for assisting people with disabilities. The results could help to inform guidelines and recommendations for policies, practices, and interventions to help alleviate poverty among people with disabilities.